2017
DOI: 10.2174/1389557517666170425105727
|View full text |Cite
|
Sign up to set email alerts
|

Atranorin - An Interesting Lichen Secondary Metabolite

Abstract: In conclusion, atranorin seems to be an interesting lichen substance, which needs to be investigated in more detail in order to allow further applications, e.g. in pharmacy, medicine or cosmetology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Lichens are an interesting taxonomic group; the organisms composed of cells of algae and fungi producing specific compounds, rare among the substances of natural origin, belong to this group. Their various biological properties include antimicrobial activity, known for a long time, as well as, researched in recent years, antioxidant and antitumor properties, resulting in inhibiting enzymes, antidiabetic, analgesic and anti-inflammatory activities [2,3]. The following paper is a review of the research on the little-known anti-inflammatory properties of lichens, drawing attention to the diversity of lichen substances, and effect of the individual compounds and extracts, whose inhibitory effect on the inflammatory processes was confirmed in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Lichens are an interesting taxonomic group; the organisms composed of cells of algae and fungi producing specific compounds, rare among the substances of natural origin, belong to this group. Their various biological properties include antimicrobial activity, known for a long time, as well as, researched in recent years, antioxidant and antitumor properties, resulting in inhibiting enzymes, antidiabetic, analgesic and anti-inflammatory activities [2,3]. The following paper is a review of the research on the little-known anti-inflammatory properties of lichens, drawing attention to the diversity of lichen substances, and effect of the individual compounds and extracts, whose inhibitory effect on the inflammatory processes was confirmed in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Rain and snow have not dissolved or washed out these metabolites from the faecal material and have not lowered their concentration in our samples. Storeheier et al (2002) reported the medium range of digestibility of different lichen species in ruminal inoculum in vitro to be between 41 and 78%, while Sundset et al (2010) reported the digestibility of lichens eaten by reindeer to amount to approximately 74%. This indicates that the total digestion of lichens may also influence the digestibility of secondary metabolites inside the lichen thalli.…”
Section: Discussionmentioning
confidence: 99%
“…Atranorin is antibacterial, but its toxicity has not been shown in animal models so far (De Melo et al 2011), while usnic acid can be toxic to both animals and humans (Dailey et al 2008) and even lethal in high doses, as shown for sheep (Durazo et al 2004). Still lichens may contribute more than 50% of the winter diet of reindeer in Subarctic and Arctic areas where lichens are an abundant part of the vegetation (Borch-Iohnsen et al 1996;Svihus & Holand 2000;Storeheier et al 2002;Denryter et al 2017). It is not fully understood how reindeer cope with such high intakes of lichen secondary compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature data, these lichens contain polysaccharides, anthraquinones, carotenoids, diterpenoids and steroids, aliphatic acids, amino acids, however, compounds of much interest are the secondary metabolites of phenolic nature -lichen acids, which possess a wide range of biological activity (Sharma 2013;Shcherbakova et al 2013;Gomez-Serranillos et al 2014;Bhattacharyya 2016;Studzińska-Sroka et al 2017).…”
Section: Introductionmentioning
confidence: 99%